Utilization of natural feed for growth and survival enhancement of Penaeus monodon juveniles in culture system and its effects on water quality - Shishehchian, Farshad (2000)
Shrimp feeds on the natural organisms such as plankton, bacteria and benthos. Problems in shrimp farming are due to pollution, diseases and poor feeding practices. There are several advantages in improving natural food in shrimp farming. First, water quality is very much improved since the oxygen evolved in photosynthesis is used in aerobic decomposition of organic matter. Moreover, ammonia in the water are reduced due to uptake by algae. Secondly, the digestibility and acceptability of natural food by shrimp have been well established. Understanding the contribution of natural foods in the shrimp culture system may help to increase the production and reduce the cost of farming. This study was carried out to demonstrate the importance of natural food in intensive shrimp culture system. Analysis of composition and abundance of macrobenthos in shrimp culture ponds was done by sampling the sediment from six different locations of two shrimp ponds. Gut content analysis was also performed to assess the fullness of shrimp gut. A significant negative correlation (r =-0.97, p<0.05) was also observed between the gut content and the abundance of macrobenthos in the pond bottom. There was a decline in the fullness of the shrimp foregut with the reduction of benthic populations in the pond sediments, probably indicating the importance of benthos as food for shrimp in culture system. In another field experiment the effect of bacterial product on development of benthic community in shrimp ponds, was determined. The density of polychaetes and insect-larvae was significantly (p< 0.05) higher in ponds with commercial bacteria products than the control, and also showed better feed conversion ratio (FeR). Laboratory experiments showed that the growth rate of P. monodon juvenile was significantly (p< 0.05) higher when fed with the combination of natural and artificial diets than other treatments. Survival rate was also significantly (p< 0.05) higher in those shrimp fed on natural diet compared to the others. The presence of bottom sediment significantly (p< 0.05) increased the survival rate of the shrimps. Shrimps fed with artificial diet showed significantly higher excretion of ammonia compare to the others. The results showed that unicellular algae could help shrimp to attain high growth and survival rates. In addition these algae control the water quality parameter such as ammonia-N and nitrite-No Tanks without shrimp showed significantly lower (p <0.05) rate of nitrogen change compared to the rest of the treatments, indicating that most of the nitrogenous source was from the shrimp excretion. There was no significant difference among the ingestion rates of three algal species but was relatively high with Chaetoceros calcitrans and low with Tetraselmis tetrahele. The results indicated that Penaeus monodon juvenile was able to ingest and digest the unicellular algae. Feeding with natural feed enhanced the non-specific immune system of the shrimp. The results showed that feeding on chironomid larva significantly (p<O.05) increase the survival rate when shrimp was exposed to the white spot virus (WSV). The results of this study showed that natural food play an important role in shrimp farming. The presence of suitable natural food may enhance the growth and survival of shrimps in a culture pond and improve the water and sediment quality. This study suggested that the optimum growth of shrimp could be obtained by the right combination of natural and artificial diets.